2011
DOI: 10.1186/1556-276x-6-466
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of ultrafine tetragonal BaTiO3 nanoparticles at room temperature

Abstract: A large quantity of ultrafine tetragonal barium titanate (BaTiO3) nanoparticles is directly synthesized at room temperature. The crystalline form and grain size are checked by both X-ray diffraction and transmission electron microscopy. The results revealed that the perovskite nanoparticles as fine as 7 nm have been synthesized. The phase transition of the as-prepared nanoparticles is investigated by the temperature-dependent Raman spectrum and shows the similar tendency to that of bulk BaTiO3 materials. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The presence of BaTiO 3 structure-type with orthorhombic phase can be associated with the vibration mode centered at 180 cm À1 , which shifts to 160 cm À1 for the sample with x = 0.20, and indicates the transformation from an orthorhombic to a rhombohedral phase. 25 The bands at low wave numbers are associated with network vibrations related to the substitution of Sr atoms for Ba atoms in the BaTiO 3 structure type. Figure 3 shows the SEM micrographs of the samples with x = 0, 0.05, 0.1 and x = 0.15.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of BaTiO 3 structure-type with orthorhombic phase can be associated with the vibration mode centered at 180 cm À1 , which shifts to 160 cm À1 for the sample with x = 0.20, and indicates the transformation from an orthorhombic to a rhombohedral phase. 25 The bands at low wave numbers are associated with network vibrations related to the substitution of Sr atoms for Ba atoms in the BaTiO 3 structure type. Figure 3 shows the SEM micrographs of the samples with x = 0, 0.05, 0.1 and x = 0.15.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 lists the chemical precursors used in the solgel synthesis method, metal dopant and the BaTiO 3 ceramics. All the earlier chemical syntheses reported the used of very expensive titanium sources for the fabrication of BaTiO 3 [23][24][25][26][27][28][29][30][31]. The molar concentrations of metal nitrates, stoichiometric amount of glycine, solid TiO 2 and sintering parameters used for the synthesis of BCT and BST are listed in Table 2.…”
Section: Materials Synthesismentioning
confidence: 99%
“…The presence of larger particles may interfere with the homogeneity of the liquid crystal, and thus destroy the orientation of the LC molecules, while the smaller particles lose their ferroelectric properties [7]. Previous work [9,10,[13][14][15][16] has shown that the preparation of ferroelectric nanoparticles is a difficult process. In recent years, one found new processes for the production of BaTiO 3 ferroelectric nanoparticles, including sol-gel method, hydrothermal method, molten salt method, mechanochemical synthesis or combustion synthesis [17,18].…”
Section: Methodsmentioning
confidence: 99%